Star Wars : Attack of the Clones Episode II - Lucas, George, 1944-; Hales, Jonathan; McGregor, Ewan, 1971-; Portman, Natalie, 1981-; Christensen, Hayden, 1981-; Williams, John, 1932-; Lucasfilm, Ltd.; Twentieth Century-Fox Film Corporation; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2002)
When political seperatists attempt to assasinate Senator Amidala, Obi-Wan Kenobi tries to find out why while Anakin acts as protector to Amidala and begins a forbidden affair with her.
Originally released as a motion picture in 2002.
Features: disc 1. commentary; disc 2. eight deleted scenes, digital character animation documentary "From puppets to pixels," exclusive documentaries "State of the art: the previsualization of Episode II," "Films are not released; They escape," three featurettes exploring Attack ot the clones storyline, action scenes and love story, 12 part web documentary series, "Across the stars" music video featuring John Williams, theatrical trailers and TV spots, theatrical poster and print campaign from around the world, "R2-D2: beneath the dome" mocumentary trailer, photo gallery with captions, Episode II visual effects breakdown montage, DVD-ROM weblink.
Director of photography, David Tattersall; production design, Gavin Bocquet; art directors, Ian Gracie ... [et al.]; special visual effects and animation, Industrial Light & Magic; film editors, Ben Burtt; music, John Williams.
Ewan McGregor, Natalie Portman, Hayden Christensen, Ian McDiarmid, Samuel L. Jackson, Christopher Lee.
MPAA rating: PG.
DVD, Dolby digital 5.1 surround.
Keywords: Vader, Darth (Fictitious character) -- Drama; Kenobi, Obi-Wan (Fictitious character) -- Drama; Star Wars films; Video recordings for hard of hearing people; Feature films; Action and adventure films; Science fiction films